Pengaruh Keberadaan Perkebunan Kelapa Sawit PT. Sapta Karya Damai terhadap Kondisi Sosial Ekonomi Masyarakat Desa Natai Baru, Kecamatan Metaya Hilir Utara, Kabupaten Kotawaringin Timur - Briliyanti, Rahma Dita; Puruhito, Dimas Deworo; Listiyani (AGRIFITIA : Journal of Agribusiness Plantation, 2024)
The existence of oil palm plantation companies cannot be denied to have an influence on the surrounding community, this influence can be in the form of positive and negative impacts. Vice versa, the views or actions of the community around the company can affect the sustainability of a company in a particular area. How does the existence of PT Sapta Karya Damai's oil palm plantation affect the socio-economic conditions of the community in Natai Baru Village, Utara Mentaya Hilir District, Timur Kotawaringin Regency. The method used in the research is the Mix Method method is a research method that combines quantitative methods with qualitative methods to be used together in a research activity. Social Conditions, before the existence of oil palm plantations (PT. Sapta Karya Damai) the education level of respondents in Natai Baru Village was low. But along with the company, the level of children's education is classified as good because there are already supporting facilities and infrastructure. Community leadership and participation in organizational membership in Natai Baru Village is good, because there are several people who participate. It can also be seen from changes in Economic Conditions, the existence of oil palm plantations in Natai Baru Village not only opens up employment opportunities, but has a direct influence on the income of people who work in oil palm plantations. The fixed income obtained by the community is of course very helpful for people's lives, such as increasing community income and fulfilling their life needs. Not only that, the community also has ownership of valuable assets such as private house ownership, ownership of motor vehicles and cars and most of the community already owns electronic assets.